Analisis Struktur dan Genre Mikro Dalam Penulisan Artikel Ilmiah : Penelitian - Jihan Fazillah; Claudya Stefany Tondang; Debora Cecilia Hutagalung; Natasya Sianturi; Fitriani Lubis (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the text structure and micro genres in scientific article writing and examine their relation to the quality of academic writing. The research employed a descriptive qualitative approach using content analysis on three scientific articles selected based on the criteria of being published in journals and having a complete structure. The research instrument consisted of an analysis sheet designed to identify the completeness of article structure elements (abstract, introduction, literature review, methodology, results, discussion, conclusion) and micro genre elements (abstract, exposition, review, reconstruction, description, discussion). The findings indicate that all three articles fulfilled the main structure of scientific writing, although differences appeared in the literature review section, which was absent in one article. In terms of micro genres, abstract, exposition, description, and discussion consistently appeared, while review and reconstruction were not present. These results highlight that variations in structural and micro-genre elements are influenced by the type of research and the author’s writing style. This study underscores the importance of understanding structure and micro genres for students and novice researchers to produce more systematic, argumentative, and academically appropriate scientific articles.